2010
DOI: 10.1038/cr.2010.5
|View full text |Cite
|
Sign up to set email alerts
|

Dual-specificity histone demethylase KIAA1718 (KDM7A) regulates neural differentiation through FGF4

Abstract: Dimethylations of histone H3 lysine 9 and lysine 27 are important epigenetic marks associated with transcription repression. Here, we identified KIAA1718 (KDM7A) as a novel histone demethylase specific for these two repressing marks. Using mouse embryonic stem cells, we demonstrated that KIAA1718 expression increased at the early phase of neural differentiation. Knockdown of the gene blocked neural differentiation and the effect was rescued by the wild-type human gene, and not by a catalytically inactive mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
110
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(113 citation statements)
references
References 60 publications
2
110
1
Order By: Relevance
“…In agreement with the latter studies, we showed that in all assays PHF8 exhibited histone demethylase activity with H3K9me2/1 specificity. In this regard, PHF2 was reported to be an H3K9me1 demethylase [34], whereas KIAA1718/KDM7A exhibits a dual H3K9 and H3K27 demethylase activity [35].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the latter studies, we showed that in all assays PHF8 exhibited histone demethylase activity with H3K9me2/1 specificity. In this regard, PHF2 was reported to be an H3K9me1 demethylase [34], whereas KIAA1718/KDM7A exhibits a dual H3K9 and H3K27 demethylase activity [35].…”
Section: Discussionmentioning
confidence: 99%
“…Previously we identified KIAA1718 (KDM7A) as a dual-specificity histone demethylase for H3K9me2 and H3K27me2 that regulates neural differentiation by controlling the expression of FGF4 [28]. To further understand how KDM7A binds chromatin and regulates transcription, we studied its Caenorhabditis elegans ortholog.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al showed that KIAA1718 (KDM7A) is required for the demethylation of H3K9me2 and H3K27me2 at the promoter region of the FGF4 gene by ChIP assay, and KIAA1718 is required for FGF4 transcription in mouse embryonic stem cells [12]. Since the expression levels of KIAA1718 are significantly higher than those of PHF8 in neuronal precursor cells [12], KIAA1718 might be responsible for the specific regulation of these H3 epigenetic markers at the FGF4 gene at this stage. Tissue or stage specific functions may be a reason for the large number of different JmjCdomain-containing demethylases.…”
mentioning
confidence: 99%